Lengua minoritaria y docencia, ¿insatisfacción laboral o síndrome de burnout? reflexiones de los maestros de aragonés sobre casi dos décadas de su enseñanza en la educación infantil y primaria - Campos, I.O. (2018)
Aragonese is one of the regional languages spoken in Aragon. Although it has not a cooficial status in the territory where it is spoken, there are some laws that recognize its value as one important element of the Aragonese culture. In spite of its arrival at some schools as a subject almost two decades ago, Aragonese teaching has been little developed. This fact, together with the unestable and variable Aragonese teacher corps, took us to question ourselves about the degree of job satisfaction among Aragonese teachers. With the aim of contribute to the knowledge of the situation, we performed a qualitative research study using Grounded Theory analyses. In each interview, we focused on four main themes: attitudes towards Aragonese language and its teaching among the educational community, the evolution of their own attitudes as ‘Aragonese language teachers’, the situation with regard to the available training and learning-resources, and the methodologies implemented. We used a non-probability sampling (concretely snowball sampling) because of the small size of the universe we were interested in. We collected the impressions of 15 of the 17 people that have taught Aragonese in the schools of Alto Aragon since 1997/1998. The data were analyzed under grounded theory procedures. We extracted the main topics and also their categories and subcategories directly from the data corpus and we reviewed the literature simultaneously. Our results show that there’s an overall situation of job dissatisfaction among Aragonese language teachers and there also are some clear cases burnout syndrome.